A venue-based analysis of the reach of a targeted outreach service to deliver opportunistic community NHS Health Checks to 'hard-to-reach' groups. (August 2016) - Roberts, D.J.; de Souza, V.C.
Abstract: Objectives: Opportunistic outreach services have been commissioned to overcome potential barriers to uptake, by offering health checks in accessible community venues. This study aimed to evaluate the ability of an outreach health check service to reach key target groups: men, people of South Asian ethnicity and people from deprived areas. The comparator was the health check service provided by GP practices. One aim was to investigate whether the addition of an outreach service would result in a higher percentage of health checks being done for people from the target groups compared to a GP-based service alone. The second aim was to assess which types of venues used for outreach health checks were most effective in reaching these groups. Study design: Evaluation of Public Health Programme with retrospective control group comparison. Methods: The percentages of completed health checks in men, people of South Asian ethnicity, and participants registered at general practices with lowest quintile area-level deprivation status were compared between all opportunistic community checks conducted by the Outreach Service over a ten month period and checks conducted in general practice in a partially-overlapping time period of the same financial year. For the venue-based comparison of Outreach Service checks, the number of checks per visit and percentage of checks in each target group were calculated for each venue. Results: Of 3849 Outreach Service checks, 38% were in men (compared to 50% of checks conducted in Primary Care), and 11% were in people of South Asian ethnicity (compared to 3% in Primary Care). 3558 Outreach check participants were registered with a general practice in the County (92%), and of these, 32% of checks were in people registered with a general practice in the lowest deprivation quintile (compared to 13% of checks in Primary Care). There were 519 visits by the outreach service to 23 different types of venue. Certain venues recorded large numbers of checks e.g. supermarkets and libraries, but they were not always the most efficient places to recruit people for checks. Mosques and bus stations were the venues with the broadest reach to all target groups. Other venues, despite having lower turnover or recruitment rates, were still good settings to reach specific target groups. Conclusion: The NHS Health Check can successfully be targeted at people from deprived areas and people of South Asian ethnicity using a targeted opportunistic community outreach approach. Our findings show that the reach to different groups varies substantially by venue, and therefore best results may be achieved by combining venues and strategies specific to the target group. Highlights: We compared the reach of health checks delivered in Primary Care to an opportunistic outreach service. We also compared the reach of different outreach venues to deliver opportunistic checks. A significantly higher percentage of outreach checks were in 'hard to reach' groups. The reach to different groups varies substantially by venue.